The echo of memory: necropolitics and resistance in the work American Indian Stories by Zitkála-Šá - BRITO, Yrlan de Sousa (2024)
This work aims at the literary analysis of the work “American Indian Stories” (1921) by the Native American writer and indigenous activist Zitkála-Ša, in order to examine which elements the author focuses on when portraying her individual and collective memories and how these stand out within the narrative. Furthermore, it highlights how the author's process of resistance opposes the impositions of the state that holds power and its manifestations of necropolitics. To compose this work, we drew on the critical fortunes of authors such as Tânia Sarmento-Pantoja (2023), Alfredo Bosi (1996) to address the concept of Resistance; Achille Mbembe (2011) on questions about Necropolitics and Olga Von Simnson (2000) on Memory and Culture.